Ease in, Ease Out, value graph Analisis Graph Editor Ease In dan Ease Out dengan Value Graph - AYADDIN DAMU (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2018)
Animation ease in and ease out the value of graph is crucial dal am workmanship every frame count with a movie shot is limited, due to address the limited frame count using value graph to adjust ease in and ease out. There are two methods used in this research that the value graph and deviation deviation (standard deviation). Value graph is the coordinate value of a graph that can affect the movement and position of the character in 3D animation, while the deviation deviation (standard deviation) is a statistical value used to determine how the distribution of data in the sample and how close the individual data points of the average value of the sample. Observation data used is swing and pendulum animation. Animation swing version has 3 pieces each have a value range on the 2 first keyframe graph respectively -120, -100 and -130 with an average deviation deviation 67.69680305, 79.60766893, 52.79835856. While pendulum aniamsi has 3 pieces of each version has the average range value graph on keyframe 4-11 is 10,07379, 14, 83451, 26,25119 with deviation deviation 7,211590762, 9,191676474, 14,50964475. Based on the qualitative test animation expert respondents as many as 15 people can be concluded that in the swing, animation has the greatest deviation graph deviation value 79.60766893 quality ease in and ease out the best 73.3%. While. At the pendulum animation, the animation has a qualitative test against animation expert respondents as many as 15 people can be concluded that the pendulum animation, the animation has a deviation value deviation graph 9.191676474 quality best ease in ease out by 66.7%.